LOCAL GOVERNMENT POLICY IMPLEMENTATION : ONE-WAY ROAD IN SELATPANJANG DISTRICT, MERANTI REGENCY INDONESIA - Moza Dela Fudika; Ellydar Chaidir; Umi Muslikhah (International Conference On Law And Social Sciences, 2024)
After the third amendment to the 1945 Constitution, Indonesia officially adopted a dualistic judicial review system. With this dualistic system, the authority for judicial review is spread/divided between two judicial organs by separating the scope of their respective tests: the Supreme Court reviews regulations under the law against the law (legal review) while the Constitutional Court reviews the law against the Constitution (constitutional review). Viewed from the perspective of theory and practice adopted by countries that adopted the formation of the Constitutional Court (a centralized judicial review model), the system adopted by Indonesia turns out to be very unusual and even a mistake in designing the judicial review system. Because in countries that have a Constitutional Court, the authority for judicial review will definitely be concentrated/centered on the Constitutional Court. This division of authority into two review regimes (legal review and constitutional review) as practiced in Indonesia is never known (except in South Korea) both in countries that use a centralized judicial review model and a distributed judicial review model. Because such a division would disrupt the implementation of the judicial review itself because the authority would be exercised by two different institutions using different testing standards. For this reason, at the end of this research, a proposition is put forward to centralize the authority of judicial review to the Constitutional Court so that the practice of dualistic judicial review which has proven to be problematic can be ended and the judicial review system in Indonesia can be reconstructed and placed on an appropriate theoretical and practical basis.